Kajian Kelayakan Sumber Air Tanah UIN Sunan Ampel Surabaya dalam Rangka Menuju Eco Campus - Fadhillah, Ninik; Ma’arif, Muh.; Faizah, Hanik; Chilmi, Latifatoel (Al-Ard: Jurnal Teknik Lingkungan, 2019)
UIN Sunan Ampel requirements of water are fulfilled from groundwater sources. The groundwater sources of UIN Sunan Ampel are from wells where the water is taken with a water pump. The main problem related to the use of groundwater as a fulfillment of water needs is the decline of its quality. The purpose of this study is to analyze the quality of groundwater at UIN Sunan Ampel, to know the quality of groundwater in UIN Sunan Ampel reviewed by Minister of Health Regulation No. RI. 32 of 2017, Formulating the right steps in improving the quality of ground water at Sunan Ampel UIN towards ECO CAMPUS. This research is a descriptive study, in this study the quality of groundwater sources in Sunan Ampel Surabaya UIN will be described base on 3 parameters of water quality (physics, chemistry and biology). The results indicate differences in groundwater quality at UIN Sunan Ampel in terms of physical, chemical and biological parameters. The quality of groundwater sources in UIN Sunan Ampel Surabaya 95% fulfills the standard of environmental health standards and water health requirements for government sanitation hygiene requirements based on physics parameters, but it do not fulfilled the quality standards based on chemical parameters (in the form of pH) and also biology parameters. Improving the quality of ground water at UIN Sunan Ampel Surabaya is needed by improving the management system of sewers and latrines as well as standard construction of wells.